Effect of surface stability on core muscle activity for dynamic resistance exercises - Willardson, J. M.; Fontana, F.; Bressel, E. (International Journal of Sports Physiology and Performance, 2009)
Purpose: To compare core muscle activity during resistance exercises performed on stable ground vs. the BOSU Balance Trainer. Methods: Twelve trained men performed the back squat, dead lift, overhead press, and curl lifts. The activity of the rectus abdominis, external oblique abdominis, transversus abdominis/internal oblique abdominis, and erector spinae muscles was assessed. Subjects performed each lift under three separate conditions including standing on stable ground with 50% of a 1-RM, standing on a BOSU Balance Trainer with 50% of a 1-RM, and standing on stable ground with 75% of a 1-RM. Results: Significant differences were noted between the stable 75% of 1-RM and BOSU 50% of 1-RM conditions for the rectus abdominis during the overhead press and transversus abdominis/internal oblique abdominis during the overhead press and curl (P < .05). Conversely, there were no significant differences between the stable 75% of 1-RM and BOSU 50% of 1-RM conditions for the external obliques and erector spinae across all lifts examined. Furthermore, there were no significant differences between the BOSU 50% of 1-RM and stable 50% of 1-RM conditions across all muscles and lifts examined. Conclusions: The current study did not demonstrate any advantage in utilizing the BOSU Balance Trainer. Therefore, fitness trainers should be advised that each of the aforementioned lifts can be performed while standing on stable ground without losing the potential core muscle training benefits.